Coordination in prototyping high-precision composite aviation parts with connectors and joints based on reverse engineering - Valeriy Sikulskyi; Kateryna Maiorova; Iryna Voronko; Oleksandra Kapinus; Oleksandr Skyba (Авіаційно-космічна техніка та технологія)
The subject of this article is the prototyping of complex high-precision aviation parts with connectors and joints, which is performed using reverse engineering methods. The focus is on ensuring geometric accuracy, which is critically important for the functionality and reliability of aviation equipment. This article analyzes methods for manufacturing parts, such as casting, machining on numerically controlled (CNC) machines, and additive manufacturing. The goal is to develop reverse engineering technology for high-precision parts that includes methods for minimizing geometric parameter errors of connectors and joints during prototype manufacturing. Tasks: analyze approaches to determining the accuracy of manufacturing parts and their joints; develop a method for calculating dimensional chains to assess errors in coordination of geometric parameters; compare the accuracy of the prototypes manufactured by casting and metal 3D printing; and propose methods to improve prototyping accuracy using a system of gauges and counter-gauges. The methods used are: the theory of dimensional chains for calculating errors; experimental analysis of casting and metal 3D printing processes to assess accuracy; development of technological operation schemes to ensure high joint precision. The following results were obtained: The accuracy of prototypes manufactured by additive manufacturing approaches was better than that of casting, but additional methods were required to reduce deviations. The system of gauges and counter-gauges allows for reducing joint alignment errors in the range of 0.121 to +0.121 mm, ensuring compliance with the technical requirements for aviation components. Conclusions: The scientific novelty of the work lies in the development of a methodology for determining and minimizing the coordination errors of parts, particularly connectors and joints, through the integration of a system of gauges and counter-gauges. The proposed methodology ensures precision manufacturing of complex aviation parts with connectors and joints. The results confirmed the feasibility of using additive manufacturing technologies for high-precision parts.